A healthy office and healthy employees: a longitudinal case study with a salutogenic perspective in the context of the physical office environment. Issue 1 (17th February 2022) - Forooraghi, Melina; Cobaleda-Cordero, Antonio; Babapour Chafi, Maral
ABSTRACT: This two-wave study (time lag of six months and two years post-relocation) investigated ways in which employees' perceptions of the office environment relate to their perceived health in the long term, drawing on the salutogenic approach to health and the sense of coherence theory (comprehensibility, manageability, and meaningfulness). A mixed-method approach was adopted. The data collection involved semi-structured interviews with employees, plus structured observations. The findings indicate that employees found the office environment less comprehensible and meaningful in Wave 2, while (somewhat) equally manageable. Comprehensibility was influenced by a lack of clear behavioural rules; manageability was influenced by a lack of control over the environment; and meaningfulness was influenced by social environment and lack of personalization. The contextual aspects of the office, including tasks, flexible working culture and the change processes were critical to these findings. This study has demonstrated that negative influences caused by poor design choices do not resolve themselves over time. When there is limited support for one component of sense of coherence, the initial observed benefits wear off and negative influences may spill over into other components. Therefore, office design should be approached with balanced attention to comprehensibility, manageability, and meaningfulness.